Smart women and small business : - Wilmerding, Ginny (John Wiley & Sons, 2006)
Are you one of the many women out there who needs a brand-new model for your business career? Are you looking for entrepreneurial alternatives to the world of big business, but aren’t sure where to start? A transition into small business is a natural progression for countless women who have invested the first phase of their careers in large companies. Many mid-career women dream of starting their own businesses, but until now there hasn’t been a book that gives them the sense of multiple choice that helps them find the right entrepreneurial fit—options that go beyond starting a venture to include buying an independent business or a franchise, joining or consulting for small businesses, or working with partners.